Tumor-infiltrating Tim-3+ T cells proliferate avidly except when PD-1 is co-expressed: Evidence for intracellular cross talk. (2nd October 2016) - Li, Jing; Shayan, Gulidanna; Avery, Lyndsay; Jie, Hyun-Bae; Gildener-Leapman, Neil; Schmitt, Nicole; Lu, Bin Feng; Kane, Lawrence P.; Ferris, Robert L.
ABSTRACT: Programmed Death 1 (PD-1) and T cell Ig and mucin domain-3 protein (Tim-3) are immune checkpoint receptors highly expressed on tumor infiltrating T lymphocytes (TIL). PD-1 inhibits T cell activation and type-1 T cell responses, while Tim-3 is proposed to mark more extensively exhausted cells, although the mechanisms underlying Tim-3 function are not clear. Trials of anti-PD-1 therapy have identified a large subset of non-responder patients, likely due to expression of alternative checkpoint molecules like Tim-3. We investigated the phenotypic and functional characteristics of T cells with differential expression of PD-1 (high/low) and Tim-3 (positive/negative), using TIL directly isolated from head and neck squamous cell carcinomas (HNSCC). Unexpectedly, we found that expression of Tim-3 alone does not necessarily mark TIL as dysfunctional/exhausted. In Tim-3-TIL, PD-1 levels correlate with T cell dysfunction, with a PD-1 low/intermed phenotype identifying recently activated and still functional cells, whereas PD-1 hi Tim-3 − T cells are actually exhausted. Nonetheless, PD-1 intermed cells are still potently suppressed by PD-L1. PD-1 expression was associated with reduced phosphorylation of ribosomal protein S6 (pS6), whereas Tim-3 expression was associated with increased pS6. Using a novel mouse model for inducible Tim-3 expression, we confirmed that expression of Tim-3 does not necessarily render T cells refractory to further activation. These results suggest the existence of PD-1 and Tim-3 crosstalk in regulating antitumor T cell responses, with important implications for anti-PD-1 immunotherapy.